40 The BNP genetic variant rs198389: hypertension risk and cardiovascular phenotype in stage A and stage B heart failure subjects from the STOP-HF trial. (October 2018) - Ledwidge, M; Cannone, V; Watson, C; Burnett, J; McDonald, K
Abstract : Background: Heritability is estimated to account for up to half of hypertension risk, yet relatively few single nucleotide polymorphisms have been associated with blood pressure in genome wide studies. B-type natriuretic peptide (BNP) possesses blood pressure lowering, natriuretic, antifibrotic and aldosterone suppressing properties. In the general population, the minor G allele of the BNP genetic variant rs198389 is associated with higher circulating values of BNP, lower blood pressure and odds of hypertension. Purpose: We aimed to investigate the clinical phenotype and cardiovascular risk associated with rs198389 genotypes in subjects at risk for heart failure (HF) dependent on whether they were stage A or B. Methods: We genotyped 971 subjects with stage A or B HF from the cohort of the STOP-HF Trial defined as the presence of at least one risk factor for the development of HF in the absence (stage A) or presence (stage B) of cardiac structural or functional abnormalities. Results: The frequencies of the rs198389 genotypes were AA: 38% (n=367), AG: 47% (n=455), GG: 15% (n=149). All subsequent analyses are AA vs GG. The two genotypes did not differ in terms of age and sex. In the multivariate adjusted analysis, the GG genotype had significantly higher circulating levels of BNP (36.3 vs 50.7 pg/mL, p value<0.001). When we evaluated the change in BNP levels over the same time period, the two groups increased by similar amount (around 5 pg/mL per annum) maintaining their significantly different set point over time. The two genotypes did not differ in terms of blood pressure, body mass index, creatinine levels at baseline. However, prevalence of hypertension was significantly lower among the homozygotes for the G allele (77.7% vs 67.1%, p value: 0.01). In the 4.95 (IQR 3.26–6.61) years follow-up analysis, the carriers of the GG genotype had lower risk of new onset left ventricular systolic dysfunction with ejection fraction <50% and more than 5% decrease (4.4% vs 0.67%, p value: 0.03). Greater differences between AA and GG genotypes, in terms of BNP levels and baseline hypertension, were seen in patients with stage B vs stage A at baseline. Conclusion: In the STOP-HF Trial cohort, the G allele of the BNP genetic variant rs198389 is associated with higher circulating BNP, lower prevalence of hypertension and lower risk of incident left ventricular systolic dysfunction over time. These associations were stronger in stage B versus stage A patients at baseline. Our findings may support the concept of a natriuretic peptide-based therapy for prevention of early stage HF in patients with stage B HF, currently under investigation in the PARABLE study.